Determinants of Stock Returns: The Role of Financial Performance and Corporate Social Responsibility - Uswatun Hasanah; Hendra Galuh Febrianto; Dhea Zatira (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study examines the effect of EPS, ROA, DER, and CSR on stock returns of companies listed in the LQ45 index during 2020–2024. Using a quantitative approach with panel data regression, 15 firms (75 observations) were selected through purposive sampling and analyzed using EViews 13. The results indicate that EPS and ROA have a positive and significant effect on stock returns, emphasizing the importance of profitability. DER shows no significant effect, suggesting leverage is not a key consideration for investors. Meanwhile, CSR has a negative and significant effect, implying it may be perceived as a cost reducing short-term gains. Collectively, all variables significantly influence stock returns, offering insights into investor behavior during the COVID-19 and post-pandemic period.